2011
DOI: 10.1121/1.3531805
|View full text |Cite
|
Sign up to set email alerts
|

A lumped mucosal wave model of the vocal folds revisited: Recent extensions and oscillation hysteresis

Abstract: This paper examines an updated version of a lumped mucosal wave model of the vocal fold oscillation during phonation. Threshold values of the subglottal pressure and the mean (DC) glottal airflow for the oscillation onset are determined. Depending on the nonlinear characteristics of the model, an oscillation hysteresis phenomenon may occur, with different values for the oscillation onset and offset threshold. The threshold values depend on the oscillation frequency, but the occurrence of the hysteresis is inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Since the target consonant here initiated a stressed syllable and the word was in a prosodicallyfocused position, f0 was generally higher on the second vowel of the sequence. Some component of the offset-onset differences observed here must be ascribed to these f0 differences (Lucero, 2005;Lucero and Koenig, 2007;Lucero et al, 2011;Solomon et al, 2007;Verdolini-Marston et al, 1990), as well as the consonant and vowel effects discussed below. These contextual factors provide an explanation for why the offset-onset differences found here are larger than those observed in past studies.…”
Section: Discussionmentioning
confidence: 92%
“…Since the target consonant here initiated a stressed syllable and the word was in a prosodicallyfocused position, f0 was generally higher on the second vowel of the sequence. Some component of the offset-onset differences observed here must be ascribed to these f0 differences (Lucero, 2005;Lucero and Koenig, 2007;Lucero et al, 2011;Solomon et al, 2007;Verdolini-Marston et al, 1990), as well as the consonant and vowel effects discussed below. These contextual factors provide an explanation for why the offset-onset differences found here are larger than those observed in past studies.…”
Section: Discussionmentioning
confidence: 92%
“…The symmetric case, with x r ¼ x ' , has been thoroughly analyzed in previous works under a variety of configurations (e.g., Lucero et al, 2011), and it has been found to provide a good characterization of experimental data from both human subjects (Lucero et al, 2012a) and mechanical replicas of the vocal folds (Lucero et al, 2012b).…”
Section: A Basic Equationsmentioning
confidence: 98%
“…Following previous work (Laje et al, 2001;Lucero et al, 2011), each vocal fold is represented by a lumped mass-damper-spring oscillator of the form…”
Section: A Basic Equationsmentioning
confidence: 99%
“…Studies with physical models (Titze et al, 1995;Chan et al, 1997;Mau et al, 2011;Mendelsohn and Zhang, 2011), computer simulation models (Pickup and Thomson, 2011), and analytical calculations (Titze, 1988b;Lucero, 1998;Chan and Titze, 2006;Klemuk et al, 2010;Lucero et al, 2011;Fulcher et al, 2012) have shown that a near rectangular glottis (as viewed in the coronal plane) produces the lowest oscillation threshold pressure. (Direct measurement of this configuration in human subjects has not been reported.)…”
Section: A Criterion For Optimal Adductionmentioning
confidence: 99%